Hafsteinshús, Huvudmodell (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2024)
Hafsteinshús, one of Högna Sigurðardóttir-Anspach early private villas, was designed and built between the years of 1965-1968. This is the result of a combination of modern brutalism and traditional Icelandic building methods. Orthogonal concrete covered by hill-sides. It is in the clefts, between the hill-sides where light finds its way into the building and where the entrances are located. The house has a residential volume and a volume that was meant as a carport but this was later converted into an art studio. Even though the building in many ways represents the brutalist architecture style, Högna challenged the rules of the style by adding organic inspired shapes. Eg. the shower walls, the reading corner and the kitchen ceiling. The heart of the building, the fireplace, is surrounded by couches sunken into a lower slab. The social spaces are not strictly divided, rather obvious in the open space. Sliding walls makes different room configurations possible. In the east corner of the building, originally designed to be the childrens area, you can screen of both the living spaces and the smaller rooms closest to the windows. In addition, this part of the house has its own entrance, a practical feature as the children grow older and might want enclosed private space.